CIKAL BAKAL TOTAL QUALITY MANAGEMENT (TQM) PADA PERUSAHAAN JEPANG DAN IMPLEMENTASINYA PADA PERUSAHAAN-PERUSAHAAN DI INDONESIA - Puji Isyanto (Jurnal Manajemen dan Bisnis Kreatif)
ABSTRAK This study aims to examine total quality management in Japanese companies and their implementation in companies in Indonesia. This research method uses descriptive analysis method. Total Quality Management that binds to Japanese companies is inseparable from Kaizen culture, so that Japan applies the principle of customer satisfaction, Quality Function Development (QFD), employee empowerment and continuous improvement for the company. Product development carried out by Japanese companies is to meet market segments with international standards and on the quality side of the product. Continuous improvement in various fields, respect and teamwork are the keys to the success of Total Quality Management in Japanese companies. Japanese companies are identified as having long-term time horizons. Companies in Indonesia can adopt total quality management well so they can create excellence. Keywords: total quality management, kaizen, continuous improvement.